Интегральные микросхемы: справочник / [Тарабрин Б. В. [и др.] - Тарабрин Б. В. (Энергоатомиздат, 1985)
Экземпляры: КХ (20060126) / Инвентарный номер: 848118 / Сис.шифр: 621.38 / Авт.знак: И 73 / ГРНТИ: 47 / ББК: 3